Kesenjangan Sosial antara Masyarakat Kelas Buruh dengan Masyarakat Elit - Mochammad Mansur; M. Qomarul Huda; Taufik Alamin; Trimurti Ningtyas; Asy’ari Asy’ari (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss the shape of the gap between the working class society and the elite society. This study uses a qualitative method with a phenomenological approach, which studies visible symptoms that arise from humans that depart from human experience itself. The results and discussion of this study show that the social class that distinguishes between workers and people who have power over them becomes a space for class struggle expressed by Karl Marx where workers try to fight against exploitation by capitalists, in this case the gap Social development is very visible when education is supposed to be able to reconstruct the thinking of the workers to fight against the elite class of capital owners who have been exploiting themselves. This study concludes that the power of the owners of capital in controlling the tools at work causes the working class to have dependence on the elite class.